Intercultural Competence Development in Comenius Project "Me and My Europe: Intercultural Challenges of Modern Pre-Primary Education" Participants at Pre-Primary Education - Līduma, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper maximizes on the reflections on the Comenius project “Me and My Europe: Intercultural Challenges of Modern Pre-Primary Education” (implementation period 2012-2014) procedures in 9 states (Latvia, Lithuania, Estonia, Poland, Italy, Spain, Portugal, Island, Turkey). The Lifelong Learning Programme documents, Latvia Ministry of Education and Science documents on preschool education, preschool guidelines by CiCe and findings on competences by the scientist Spona are at the theoretical basis. The content describes the acquisition of the intercultural competences in team workshops and Art Labs. The project served as a tool to promote intercultural competences (knowledge, skills, attitudes and self-experience) of the project participants (teachers, parents and young learners) and was attested by help of discussions, observations and a questionnaire.